Kajian bukaan praktikal untuk gaun wanita mengandung. - Anizan, Omar (Universiti Malaysia Sarawak (UNIMAS), 2007)
This study is to design a value added maternity dress with functional openings. The aim is to help pregnant lady access their tummy area for common medical check – up and to apply lotion, which is frequently needed during this period. The design covers overlay, front side openings with invisible zips, loops with button and Velcro strips to give easy opening and access of their tummy without revealing other body part. The selection of design is focused on casual wear using natural fiber fabric which aims to give comfort and ease as well as aesthetic value to consumers